Экологизация экономики рынка: [учебное пособие] (О. П. Литовка, Л. А. Дедов, К. В. Павлов, М. М. Федоров ; Институт проблем региональной экономики [и др.]) - Литовка Олег Петрович (2015)
Режим доступа: http://eanbur.unatlib.ru/handle/123456789/874 Экземпляры: ЭАНБ (20150924) / Инвентарный номер: PDF002764 / Цена: / Сис.шифр: 65.9(2)28 / Авт.знак: Э 40 / ГРНТИ: 87 / ББК: 65.28